Transcription of tufA and other chloroplast-encoded genes is controlled by a circadian clock in Chlamydomonas. - Hwang, S (1996)
Levels of mRNA for the chloroplast-encoded elongation factor Tu (tufA) showed a dramatic daily oscillation in the green alga Chlamydomonas reinhardtii, peaking once each day in the early light period. The oscillation of tufA mRNA levels continued in cells shifted to continuous light or continuous dark for at least 2-3 days. Run-off transcription analyses showed that the rate of tufA transcription also peaked early in the light period and, moreover, that this transcriptional oscillation continued in cells shifted to continuous conditions. The half-life of tufA mRNA was estimated at different times and found to vary considerably during a light-dark cycle but not in cells shifted to continuous light. Light-dark patterns of transcription of several other chloroplast-encoded genes were examined and also found to persist in cells shifted to continuous light or dark. These results indicate that a circadian clock controls the transcription of tufA and other chloroplast-encoded genes.